Media Cetak dan Elektronik dalam Bimbingan Penyuluhan - Rahmiyati Rahmiyati (UIN Antasari Banjarmasin, 2015)
Everything is so abstract that will certainly lead to different conclusions and perceptions could even lead to a false perception of the message being delivered. That is why the implementation of the guidance and counseling should use the media to bear on guidance and counseling is effective. It is inevitable that the tools or media is required by anyone, let alone for an extension whose primary task is always interacting with others. Thus the extension should use the media in the process of counseling. Media will be able to help the educator to convey the message that the abstract to be real, can membankitkan individual spirit and can easily arouse the consciousness of the individual. Before using an extension media should be able to choose and use the right media with activities of counseling in order to run effectively and efficiently.